(untitled) (Research, Society and Development, 2020)
The objective of this paper is presents an experience report carried out during the learning-teaching processes in the courses involving the study of algorithms, programming logic, and programming language. in the Degree in Information Systems of Federal University of Santa Maria in the city of Frederico Westphalen - RS. The report presents the strategies and results, obtained from the application of active learning methodologies, placing the student as the center of the process, an active subject in the construction of his knowledge.